Microbial profile of burn wound injuries in the Northern West Bank − A retrospective cohort study - Sameh Natsha; Hester Lacey; Souad Belkebir; Ann Attili; Aya Atatra; Rawand Daragmeh; Anas Abu-Safa; Baljit Dheansa; Rasha Khayyat (Elsevier, 2025)
Background: Determining frequently colonizing microorganisms and typical demographics affected by burns in the West Bank is essential to aid timely and effective injury management. Methods: This study included n = 435 patients with burn injuries between January 2018-December 2021 at a tertiary center in Nablus. Eligible medical records were reviewed, and relevant data extracted. Results: n = 244 males and n = 191 females, average age 14.5 years were included. n = 227 had wound swab cultures, n = 80 which were positive. Scald injuries were the most common mechanism of injury (n = 314, n = 162 in males (p < 0.001), average age of 10.5 years). The most common organisms isolated were Pseudomonas aeruginosa (n = 17) and Staphylococcus aureus (n = 18). n = 17 multidrug resistant (MDR) organisms were cultured, MRSA most commonly (n = 9), followed by K. pneumoniae (ESBL) (n = 5). Overall length of stay (LOS) was 17.27 days in all patients and 28.2 days in those with MDR, with increasing LOS significantly associated with positive culture and MDR development of MDR (p < 0.001). Conclusions: Younger male demographics and longer hospital admission increase the risk of burn wound colonization and MDR development in the Northern West Bank. Pseudomonas aeruginosa and Staphylococcus aureus were prevalent organisms isolated. MDR development represents a significant challenge in the effective management of injuries in an immunologically vulnerable cohort.